2017
DOI: 10.5958/0974-0279.2017.00006.4
|View full text |Cite
|
Sign up to set email alerts
|

Economics and Institutional Aspects of Protected Cultivation of Carnation in Himachal Pradesh

Abstract: This paper examines the role of different institutions in promotion of protected cultivation and the benefits realized by the farmers in Solan district of Himachal Pradesh. The area under protected cultivation promoted by National Horticulture Mission, has been found nearly 1.5 lakh ha, of which 20 per cent is under greenhouse. The export-oriented carnation cultivation has been observed most profitable visa -vis domestic market oriented and diversified pattern of production. The study has shown that the cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The payback period for polyhouse production of different crops is estimated to be 1.48 to 2.34 years with subsidies, and 2.51 to 4.04 years without subsidies for a 0.1 ha area. Similar results were reported by Punera [18], which indicated that the investment can be recovered within 5 years depending upon the crops grown in the polyhouse. Additionally, the internal rate of returns varies from 31% for carnation with capsicum to 73% for carnation.…”
Section: Viability Analysis Of Protected Cultivation Of Horticultural...supporting
confidence: 89%
See 2 more Smart Citations
“…The payback period for polyhouse production of different crops is estimated to be 1.48 to 2.34 years with subsidies, and 2.51 to 4.04 years without subsidies for a 0.1 ha area. Similar results were reported by Punera [18], which indicated that the investment can be recovered within 5 years depending upon the crops grown in the polyhouse. Additionally, the internal rate of returns varies from 31% for carnation with capsicum to 73% for carnation.…”
Section: Viability Analysis Of Protected Cultivation Of Horticultural...supporting
confidence: 89%
“…Among the variable costs, the human labour share to the total cost of cultivation was high for rose (35%), followed by carnation (33%), gerbera (31%) and capsicum (27%). Results were observed by Punera [18]; Sudhagar [43] reported that the planting materials and human labour cost were the major investments. Further, it was observed that the total yield obtained from the polyhouse was INR LAKH 2.22, 2.07 and 2.00 in numbers of gerbera, carnation and rose, respectively, whereas 11,325 kgs of capsicum fruit yield was obtained.…”
Section: Economics Of Polyhouse Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the worldwide scenario, there are roughly 623.30 thousand hectares under protected agriculture, compared to the world's total gross vegetable output area of 402.98 thousand hectares. According to Punera et al [7], the National Horticulture Mission's protected cultivation programme was reported to have about 1.5 lakh acres of land in Himachal Pradesh, India, in the 2014-15 growing season. According to Sabir and Singh [8], there were around 25,000 ha of protected farming in India in 2012-13, compared to 2000 ha for greenhouse vegetables.…”
Section: Scenario Of Protected Structuresmentioning
confidence: 99%
“…The sale proceeds were Rs.1095000 per year and net return as Rs.633797.35. In previous studies economic analysis of production and marketing of selected cut flowers grown under small sized Green house in Pune District [7,8], Himachal Pradesh [9,10], Haryana [11] were discussed. Jitendra [12] studied the comparative economic analysis of high tech and field rose cultivation around Bangalore city.…”
Section: Cost Of Production and Returns Of Greenhouse Rose Cultivationmentioning
confidence: 99%